Isoflavone Content in Subterranean Clover Germplasm from Sardinia. Issue 8 (5th August 2016) - Tava, Aldo; Stochmal, Anna; Pecetti, Luciano
Abstract : Subterranean clover ( Trifolium subterraneum ) is an important pasture legume, and Sardinia is known as a major centre of diversification of this species. As other legumes, this clover produces biologically active flavonoids including the subclass of isoflavones that are natural phytoestrogens with positive health effects. Present sources of isoflavones for medical/nutraceutical treatments are red clover ( Trifolium pratense ) and soybean ( Glycine max ). This study assessed the content and composition of flavonoids in 14 subterranean clover genotypes from Sardinia, grown ex‐situ in comparison with two red clover ecotypes, to acquire information on the potential of the species as an alternative source of isoflavones for possible exploitation. Twenty compounds were tentatively identified across the two clovers after HPLC and LC/ESI‐MS analyses, including clovamide, four flavonols, and 15 isoflavones. Most compounds were present as glucosides or glucosyl malonates. Subterranean clover extracts mainly comprised of derivatives of the isoflavones genistein, biochanin A, and formononetin. Compared to red clover, subterranean clover had higher content of total isoflavones and lower concentration of total flavonols. The isoflavone concentration in subterranean clover was higher than literature data for soybean or red clover. The existing genotypic variation warrants the possibility of selecting varieties with high isoflavone concentration for nutraceutical or pharmaceutical purposes. Abstract : Isoflavone Content in Subterranean Clover Germplasm from Sardinia A. Tava *, A. Stochmal, L. Pecetti